2014
DOI: 10.1080/00071668.2014.935701
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of florfenicol and florfenicol amine residues in chicken eggs

Abstract: 1. The aim of this study was to develop a suitable method for the analysis of florfenicol (FF) and its metabolite florfenicol amine (FFA) in chicken eggs and to determine FF and FFA residue depletion in eggs of laying hens. 2. The analytes were extracted from yolk, albumen and whole egg by phosphate buffer and ethyl acetate. Following purification, samples were analysed by high-performance liquid chromatography. 3. Fifty laying hens were divided into 5 groups, and each hen received doses of 20 mg/kg FF: Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…The residues of tapentadol in eggs after multiple oral dose administration in laying hens were higher in yolk than those in albumen (35). After florfenicol withdrawal, 57% of the drugs were eliminated from laying hens through the egg yolk (9). In the current study, elimination of residues of florfenicol and enrofloxacin was fastest in the egg followed by plasma while the retention time of florfenicol and enrofloxacin residue was longest in the liver and kidney, respectively.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The residues of tapentadol in eggs after multiple oral dose administration in laying hens were higher in yolk than those in albumen (35). After florfenicol withdrawal, 57% of the drugs were eliminated from laying hens through the egg yolk (9). In the current study, elimination of residues of florfenicol and enrofloxacin was fastest in the egg followed by plasma while the retention time of florfenicol and enrofloxacin residue was longest in the liver and kidney, respectively.…”
Section: Discussionmentioning
confidence: 43%
“…Florfenicol and enrofloxacin are wide-spectrum, synthetic antibacterial drugs widely used in the livestock industry, but an adequate drug withdrawal period must be ensured before marketing the animal or its products. In this context, concerns over drug residues in eggs and consumers' health have led several countries including China, UK, and USA to ban the use of florfenicol and enrofloxacin in diets of laying hens (8)(9)(10). However, oftentimes, poultry veterinarians have no choice but to use these drugs for treatment from the perspective of animal welfare and therapeutics (6).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 72% of egg samples have shown positive results, whereas only 28% of samples presented negative results. Another study showed the presence of FF in eggs as 57% of the drug was eliminated from egg yolk (Filazi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA analysis was undertaken as described above. The HPLC method was performed on the basis of procedures performed by the former literature with some modifications (Filazi et al, 2014;Xie et al, 2011).…”
Section: Comparison Between the Elisa And Hplcmentioning
confidence: 99%
“…Previously, many physicochemical analysis methods had been developed for FF and its metabolite determination, such as liquid chromatography (LC) (Dasenaki & Thomaidis, 2015;Imran et al, 2017;Saito-Shida et al, 2019;Xie et al, 2018), gas chromatography (GC) (Shen et al, 2009) (Azzouz & Ballesteros, 2015), and high-performance liquid chromatography (HPLC) (Filazi et al, 2014;Wang et al, 2016;Wang et al, 2019;Xie et al, 2011) combined with different detector systems. Among these methods, HPLC was the most frequently applied technique partly due to its high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%